1998
DOI: 10.1001/archopht.116.12.1583
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Glaucoma With Scanning Laser Polarimetry

Abstract: To determine which retinal nerve fiber layer (RNFL) measures obtained with scanning laser polarimetry are most useful in detecting early to moderate glaucomatous visual field loss.Subjects and Methods: One eye from 84 healthy individuals and 83 patients with early to moderate glaucomatous visual field loss (167 eyes) was assessed with a scanning laser polarimeter (Laser Diagnostic Technologies, San Diego, Calif). Three separate scans were obtained, and a baseline scan was created and used in the analyses. Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
155
3
42

Year Published

1999
1999
2005
2005

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 205 publications
(211 citation statements)
references
References 20 publications
11
155
3
42
Order By: Relevance
“…[7][8][9]17 Weinreb et al 7 found that with the exception of symmetry, there were statistically significant differences between healthy and glaucomatous eyes with GDx parameters that include the GDx number, superior ratio, inferior ratio, superior/nasal ratio, maximum modulation, superior maximum, inferior maximum, ellipse modulation, average thickness, ellipse average, superior average, inferior average, and superior integral.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9]17 Weinreb et al 7 found that with the exception of symmetry, there were statistically significant differences between healthy and glaucomatous eyes with GDx parameters that include the GDx number, superior ratio, inferior ratio, superior/nasal ratio, maximum modulation, superior maximum, inferior maximum, ellipse modulation, average thickness, ellipse average, superior average, inferior average, and superior integral.…”
Section: Discussionmentioning
confidence: 99%
“…The definitions of these parameters have been described elsewhere. 6,7 Statistical analyses were performed using JMP software (SAS Institute, Cary, NC, USA). Mann-Whitney tests with Bonferroni correction were used to evaluate differences between both study groups for the 12 standard GDx parameters, the RNFL thickness from the nasal and temporal averages, BCVA, refraction (spherical equivalent), visual field indices including mean defect (MD), and CPSD.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12] Most of these studies explored the standard parameters provided by the GDx (described elsewhere 13 ) or combinations of these (some including the built-in classifier named The Number). Despite their fair to excellent performance, these parameters may be quite insensitive to wedge defects, especially narrow ones, since they are based either on general statistics of measurements along an ellipse around the optic disc or on measurements in a fairly large area, such as an image quadrant.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] The technique is based on the optical retardation of the illuminating laser beam, which is produced by the parallel retinal nerve fibres around the optic nerve head. 6 The optical retardation caused by the retinal ganglion cell axons has been shown to have a linear relationship with the anatomical thickness of the retinal nerve fibre layer (RNFLT), and is therefore suitable for the detection of retinal nerve fibre loss.…”
Section: Introductionmentioning
confidence: 99%